Investigating engineering students' learning for global preparedness in curricular and cocurricular engineering education - Cook, Alistair, author; Korte, Russell, advisor; Siller, Thomas, advisor; Bourn, Douglas, committee member; Valdes Vasquez, Rodolfo, committee member; Birmingham, Daniel, committee member (Colorado State University. Libraries, 2019)
Engineering as a profession has a significant impact globally in the creation and maintenance of the infrastructure and technology on which humanity relies. As resource constraints and dramatic global population growth challenge engineering's ability to support sustainable, appropriate development globally, the education provided for engineers is increasingly important for preparing engineering students to face the challenges of the present and future. Therefore, it is essential to understand how engineering students can become more globally prepared in their studies. The purpose of this study is to compare, through student experiences, different classes, and programs in engineering education designed to develop students' capabilities in global preparedness. The data for this project were collected through interviews with students who were taking part in different learning curricular and cocurricular classes and programs. In addition, data were collected through pre/post/retrospective-pre-student surveys when possible (for participant groups of greater than 30). The outcomes of this study are presented in three articles. The first article is a structured literature review of the global and professional competencies recognized by academia and engineering practitioners as key experiences and learning designed to improve undergraduate engineering students' global preparedness. The second article is a mixed methods analysis, comparing on-campus classroom development of global preparedness and the impact of changing the context of the engineering class (from local to global) on student's global preparedness and professional competence development. The final article reports on the results of interviews with students participating in different study abroad and volunteer programs, to compare and contrast their experiences in and the impact of those programs. The value of this study is that universities and students may be able to use these results to better understand how to more effectively design and deliver classes and programs to increase the global and professional preparedness of engineering students.